IMPLEMENTATION OF A COMMUNITY WASTE MANAGEMENT EDUCATION PROGRAMME TO IMPROVE ENVIRONMENTAL AWARENESS IN KEBAKKRAMAT DISTRICT - Bekti Utomo; Muhammad Hendri Nuryadi; Itok Dwi Kurniawan; Wahyu Noviansyah; Ismawati Septiningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The increasing volume of waste generated in urban areas poses significant challenges to environmental sustainability. This study aims to evaluate the effectiveness of a community-based waste management education program implemented in Kebakkramat District. The primary objective is to enhance environmental awareness among residents, thereby fostering responsible waste management practices. A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews to assess community engagement and knowledge retention. Data collected from 200 households indicated a 40% increase in awareness about waste segregation and recycling practices post-implementation. Additionally, qualitative feedback highlighted a shift in community attitudes towards waste management as a shared responsibility. The findings suggest that community involvement is crucial for the success of environmental initiatives. This research contributes to the growing body of evidence supporting education as a vital tool for enhancing environmental awareness and promoting sustainable practices at the community level.